Market reactions to financial distress announcements: Does the market react differently to different outcomes? - Ahmad, Abd Halim @ Hamilton; Abdullah, Nur Adiana Hiau; Taufil Mohd, Kamarun Nisham (AccessEcon, 2016)
We examine market reactions to the financial distress announcements of listed firms in Malaysia.The sample consists of 236 financially distressed companies between 2001 and 2014. We investigate whether the market differentiates between the subsequently re-emerged and subsequently delisted firms at the time of financial distress announcements.The results suggest that there is evidence of differing reactions to distress announcements according to firms' outcomes. These results suggest that, at the time of financial distress announcements, the capital market differentiates firms based on the expected outcomes of the distress, showing that the market has insights into the expected outcomes of the financial distress.